2007
DOI: 10.1073/pnas.0707930104
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of behavior support existence of culture among wild chimpanzees

Abstract: Culture has long been considered to be not only unique to humans, but also responsible for making us qualitatively different from all other forms of life. In recent years, however, researchers studying chimpanzees (Pan troglodytes) have challenged this idea. Natural populations of chimpanzees have been found to vary greatly in their behavior. Because many of these interpopulation differences cannot be readily explained by ecological factors, it has been argued that they result from social learning and, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
4
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 45 publications
2
68
4
1
Order By: Relevance
“…codes were treated as missing values in our quantitative analyses. Our numerical coding system differs from that used in the study of Lycett et al [42,43], in that these authors did not distinguish between behavioural variants that were absent and those that were absent owing to an ecological reason.…”
Section: (B) Behavioural Analysesmentioning
confidence: 94%
“…codes were treated as missing values in our quantitative analyses. Our numerical coding system differs from that used in the study of Lycett et al [42,43], in that these authors did not distinguish between behavioural variants that were absent and those that were absent owing to an ecological reason.…”
Section: (B) Behavioural Analysesmentioning
confidence: 94%
“…Many species also exhibit cultural traditions, defined as group differences generated by social learning (Lycett et al 2007;Whiten et al 1999). Only humans, however, appear to possess cumulative cultural evolution, defined as the accumulation of beneficial modifications over successive generations (Dean et al 2014).…”
Section: What Underlies Cumulative Cultural Evolution?mentioning
confidence: 99%
“…The authors argued that these patterns could not be explained by differences in ecology, and hence concluded that at least some of these traits are likely to be culturally inherited. Considerable controversy has surrounded the problem of cultural transmission in chimpanzees, as some have argued that observed patterns could also be consistent with a genetic basis for behaviours (Laland & Janik 2006), while additional evidence has been presented based on cladistic analysis suggesting the behaviours are more likely to be culturally inherited (Lycett et al 2007(Lycett et al , 2010. As other research on chimpanzees has failed to find significant differences between patterns of variation among groups for genetic loci versus behavioural traits (Langergraber et al 2011), the extent to which these behaviours are culturally inherited remains unclear.…”
mentioning
confidence: 99%